Comparison of the Buschke Selective Reminding Test and the California Verbal Learning Test – Second Edition in a heterogeneous sample of people with traumatic brain injury. Issue 2 (4th March 2019) - Leitner, Damian; Miller, Harry; Libben, Maya
ABSTRACT: This study examined score and classification differences between the Buschke Selective Reminding Test (SRT) and the California Verbal Learning Test - Second Edition (CVLT-II) in a TBI sample. Seventy-nine participants with traumatic brain injury (TBI) were included and were comprised of 49 mild TBI, 11 moderate TBI, and 14 severe TBI. The majority of participants with mild TBI were involved in litigation. Scores were compared between the CVLT-II and SRT on the total sample and after segregating TBI severity. Correlations between the SRT and CVLT-II were variable ( r = .23 to .72). Total List score was lower on the SRT across all levels of TBI severity ( p < .006). Learning score was lower on the SRT in mild and severe TBI groups ( p < .006). Long delay free recall score was lower on the SRT in mild TBI group only ( p < .006). Across TBI severity, lower scores were found on the CVLT-II between severe and mild TBI ( p = .04). Scores on the SRT did not differ between TBI severities. The two tests appear to provide different clinical interpretations in a TBI sample. Results may be due to features of the normative data, test procedures, and/or word lists. Clinical implications and limitations are discussed.